2020
DOI: 10.1155/2020/2180913
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-451a and miRNA-125a Expression Levels in Ankylosing Spondylitis: Impact on Disease Diagnosis, Prognosis, and Outcomes

Abstract: Background. Early diagnosis of ankylosing spondylitis (AS) is yet not elucidated, with a potential diagnostic glance of microRNAs (miRNAs). Aim. Study the expression profile of miRNA-451a and miRNA-125a in AS patients and their impact on disease activity and prognosis. Methods. A cross-sectional study included 55 AS patients diagnosed according to modified New York criteria in 1984 with 55 matched healthy controls. History, clinical examination, and disease activity assessment with Bath ankylosing spondylitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To date, many attempts to screen biomarkers of AS have been made. Based on miRNA-451a and miRNA-125a expression levels ( 56 ) and collagen protein of serum samples ( 57 ), the models generally achieved the performance of AUCs between 0.60 to 0.80. Herein, we obtained a more accurate and higher AUC of 0.868, 0.895, and 0.893 using only 1004 gut vOTUs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many attempts to screen biomarkers of AS have been made. Based on miRNA-451a and miRNA-125a expression levels ( 56 ) and collagen protein of serum samples ( 57 ), the models generally achieved the performance of AUCs between 0.60 to 0.80. Herein, we obtained a more accurate and higher AUC of 0.868, 0.895, and 0.893 using only 1004 gut vOTUs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] miR‐21 and miR‐126 can be used as novel diagnostic biomarkers for acute coronary syndrome. [ 31 ] Notably, some miRNAs, such as miR‐214, [ 22 ] miR‐451a, and miR‐125a [ 32 ] have been demonstrated to be used as diagnostic biomarkers for AS patients. This study demonstrated the high diagnostic value of miR‐222‐3p to screen AS patients from healthy subjects and RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these limitations, further studies involving various age ranges and female subjects are required to gain further insights into this disease. miRNA profiling has been used as a diagnostic tool for several diseases [31][32][33][34] . We evaluated miRNAs in skin biopsy samples comprising epidermal and dermal tissues.…”
Section: Discussionmentioning
confidence: 99%